Recent Progress of Bypass Surgery to the Dialysis-Dependent Patients with Critical Limb Ischemia - Azuma, Nobuyoshi (Ann Vasc Dis, 2017)
According to expansion of dialysis-dependent population, more than half of patients with critical ischemic limbs are dialysis-dependent in Japan. Although patients with end-staged renal disease are well-known as poor life prognosis, well-managed dialysis patients in Japan can survive much longer compared to dialysis patients in the United States and Europe. Therefore, some dialysis patients can enjoy the long-term benefits of bypass surgery. To decide the indication of bypass surgery, patient’s general condition, nutrition status, and vein availability are more important rather than arterial disease anatomy. Ultrasound guided nerve block anesthesia blocking both sciatic and femoral nerve is contributing greatly to quick postoperative recovery of high risk patients. Preoperative ultrasound examination also contribute to not only vein mapping but also find out the graftable segment of artery. The selection of distal target should be decided based on the degree of arterial disease (luminal surface as well as wall calcification), and arterial run-off. Several tips regarding anastomosis to heavily calcified artery have been established including how to create bloodless operative field without arterial clamps. Adequate wound management after bypass surgery is also important. Detection of deep infection such as osteomyelitis and the adequate treatment may avoid major amputation of salvageable limbs. In the era of endovascular treatment, the evidences guiding how to select dialysis patients suitable for bypass surgery are awaiting. (This is a translation of Jpn J Vasc Surg 2017; 26: 33–39.)